Impact Of Nutsi-Smartphone Application On Nutritional Knowledge Among Breastfeeding Mothers: A Quasy-Experimental Study - Haneda Yorika Fauzia; Mekar Dwi Anggraeni; Nina Setiawati (Poltekkes Kemenkes Surakarta, 2022)
Background: Nutrition knowledge among breastfeeding mothers is a key factor in good nutrition status. Some breastfeeding mothers in Indonesia suffer from inadequate nutrition status, which may affect exclusive breastfeeding practice. However, few breastfeeding women have adequate nutritional knowledge. Health education about adequate nutrition during lactation is highly needed. Methods: This was a quasi-experimental study with a control group, pretest, and post-test design. It was conducted at the work area of the Panyingkiran Public Health Center, Majalengka Regency, West Java Province, Indonesia. This study used a consecutive sampling method and involved 78 respondents, divided into 39 respondents in the intervention group and 39 respondents in the control group. Data was collected using a set of questionnaires to collect demographic and nutritional data. Then, the data were analyzed using the Wilcoxon test and Chi-square test. Results: This study found that there was a significant difference between pre-test and post-test scores in the intervention group (t=0,000 p<0,05). There was no significant difference between pre-test and post-test scores in the control group (t=1, p >0,05). Furthermore, there was a significant difference in post-test scores between the intervention and control groups (t=0,000 p<0,05). Conclusion: The developed smartphone application-Nutsi-was effective in increasing nutritional knowledge among lactation mothers. Health care providers may use Nutsi as a health promotion media in order to improve nutrition knowledge among pregnant women.